Experiment for time domain analysis using MATLAB app designer (I) - Chew, Hoon Goek (Nanyang Technological University, 2024)
The study concentrates on the elaboration and realization of two interactive MATLAB GUI applications designed for time-domain analysis in the domain of signal processing education. The application platform GUI of MATLAB is designed to offer to the user a simple and entertaining approach to fundamental time-domain questions and techniques, including the properties of the LTI systems, the convolution, impulse response, frequency estimations as well as the impact of different filters. These programs largely focus on educational resources, interactive features, and signal processing tools as a way of encouraging self-learning and exploration. In this study, the design and application of interactive MATLAB GUI apps for time-domain analysis within the learning process of signal processing are presented. These apps me to have the user easily fundamental concepts in system of LTI these consists of convolution, impulse response, frequency response impulse, and filtering effects and so on. Adopting an end user-centered design method, apps offer a fresh interface complete with multiple help elements in the form of tooltips, explanatory text, multimedia elements, and tutorials. This interface works as a hub that connects the user to the content and enhances the ability to understand complexes contents. These multimedia-based programs, with educational content, interactive elements, and algorithm for signal processing, will help to deliver a complete learning experience. After undergoing testing on a broad scale, being re-worked with users’ feedback, and a through-and-through design, the GUI software solutions for will be a set of comprehensive tools that users will be able to use to learn more about the principles of time-domain analysis as well as their practical applications. The groundbreaking research work outlines the progress, difficulties, and the grounds for the future research in relation to the MATLAB GUI Apps for signal processing training.